Культурна пам’ять як чинник конструювання ідентичності в умовах трансформації українського суспільства - Вербицька, Поліна; Verbytska, Polina (Lviv Politechnic Publishing House, 2019)
Статтю присвячено проблемі актуалізації потенціалу культурної пам’яті як соціального інструменту в процесі конструювання ідентичності особистості. Виокремлено та узагальнено проблеми, які існують у сфері колективної, суспільної і культурної пам’яті. Розкрито феномен культурної пам’яті як рушія змін та його зв'язок із теорією прав людини як індикатора демократичних змін. З’ясовано потенціал дослідження ролі культурної пам’яті у період демократичної трансформації українського суспільства як посередника нового суспільного наративу минулого, що інтегрує різні перспективи.

The article deals with the problem of actualization of the cultural memory potential as a social tool in the process of identity construction in the conditions of the Ukrainian society democratic transformation. The main thesis of the article is that the cultural memory has mighty resources in the conditions of a democratic and lawful state, securing forming, preserving, transferring and developing of cultural norms, values, knowledge and meanings, contributing to integration, social consolidation. The representation of the historical past and of historical events which are created and disseminated in society within the limits of specific cultural markers and political context was outlined. It was found out that social memory is produced by mediated ideas of the past which represent selective, simplified inclusion and exclusion of information. It has been underlined that memorizing and forgetting are selective processes. There has been analyzed the notion “complex of memory” (according to Sharon Macdonald), which includes the interaction of three important components – memory, heritage and identity. It has been stated that actualization of historical narrative in places of memory is aimed at forming a personality’s identity, feeling of belonging to a certain community and its historical past. There has been underlined the connection between historical consciousness and cultural memory in the process of formation of a personality’s identity. It has been identified that values are an important component in the structure of historical consciousness of a personality. There has been explained the phenomenon of cultural memory as a mover of changes and its connection with the human rights theory as a democratic changes indicator. The significance of the role of human rights in the conditions of modernization and transformation has been substantiated. The role of the human rights idea in the modern transformation of Ukrainian society has been characterized. It has been allocated and summarized that recognition of the priority of human rights, human dignity gives possibility to form value attitude of an individual to memory and recollections of various individuals and communities, the willingness to transmission of values and experience of the past to other members of society, to overcome possible negative consequences of social interaction.
Cultural memory as a factor of identity construction in the conditions of Ukrainian society transformation
Keywords: ідентичність; трансформація; культурна пам'ять; права людини; місця пам'яті; identity; transformation; cultural memory; human rights; places of memory; 008; 930.85; 316.42